Isolation, Purification, and Characterization of Xylanase Produced by a New Species of Bacillus in Solid State Fermentation - Rajashri D. Kamble; Anandrao R. Jadhav (International Journal of Microbiology)
A thermoalkalophilic new species of Bacillus, similar to Bacillus arseniciselenatis DSM 15340, produced extracellular xylanase under solid state fermentation when wheat bran is used as carbon source. The extracellular xylanase was isolated by ammonium sulfate (80%) precipitation and purified using ion exchange chromatography. The molecular weight of xylanase was ~29.8 ;kDa. The optimum temperature and pH for the enzyme activity were 50°C and pH 8.0. The enzyme was active on birchwood xylan and little active on p-nitrophenyl xylopyranoside but not on Avicel, CMC, cellobiose, and starch, showing its absolute substrate specificity. For birchwood xylan, the enzyme gave a Km 5.26 ;mg/mL and Vmax 277.7 ;μmol/min/mg, respectively. In addition, the xylanase was also capable of producing high-quality xylo-oligosaccharides, which indicated its application potential not only in pulp biobleaching processes but also in the nutraceutical industry.